Manfaat Langsung Perhutanan Sosial Pada Kawasan Ekowisata Kabupaten Tanggamus - Ismalia Afriani Hasbullah; Fournita Agustina (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2018)
Social forestry area that has the potential of ecotourism drives economic analysis of agroforestry among others were directed to assess whether the resources used in agroforestry activities are already quite efficient. While the community can not rely proceeds from the farm, the tourism sector comes to be a reliable source of income to meet the community needs. This study aimed to evaluate the direct benefits gained by the community, both from farming and other business results from social forestry region. Measurement of this immediate benefit was taken by approaching to the market value to quantify price of various directly marketable commodities. The sample size set with sampling friction by 20% in each study site, while the method of sampling was done using a quota sampling method. Assessment of each alternative in determinating allocation of efficient ecosystem utilization was done by using the Cost-Benefit Analysis (CBA) and Benefit Cost Ratio (BCR). The study results showed a variety of direct benefits that gained by farmers located around bufferzone forest areas, namely; farming, ecotourism, trade, labor, livestock and fish. Farming sector is still the mainstay of income source, each farming concession on forest land have indicated the venture feasibility in financial aspect. These indicate that farm management on forestry land is able to deliver benefits to the whole society.